The Expression and Role of microRNA-133a in Plasma of Patients with Kawasaki Disease. (19th May 2022) - Luo, Yeping; Yu, Meng; Li, Pengzhu; Huang, Lihua; Wu, Jiping; Kong, Min; Li, Ying; Wu, Zhixiang; Kang, Zhijuan; Yi, Lu; Yang, Zuocheng
ABSTRACT: Kawasaki disease (KD)), also known as mucocutaneous lymph node syndrome (MCLS),  is an autoimmune and systemic vasculitis syndrome. Its etiology and pathogenesis are still unclear. microRNAs (miRNA), a novel class of small non-coding RNAs, regulate the expression of multiple protein-encoding genes at the post-transcriptional level. We intend to study the change of miRNA-133a in the plasma of patients with KD, explore the role of miRNA-133a on HUVEC and define the pathogenesis of vascular dysfunction in KD. miRNA-133a expression and the mRNA and protein expression of protein phosphatase 2 catalytic subunit alpha (PPP2CA) were assessed by RT-qPCR and Western blot, respectively. The PPP2CA mRNA 3ʹUTR was predicted to be the potential target of miRNA-133a by using the miRNA databases and verified by the luciferase assay. The plasmids of miRNA-133a mimics and inhibitors were transfected into HUVEC cells. The plasma soluble vascular endothelial cadherin (sVE-cadherin, the excised extracellular part of VE-cadherin) levels were investigated by ELISA. The results suggested that miRNA-133a was increased by 3.8 times in the acute KD group and by 2.7 times in the convalescent KD group compared with the control group (both P =  .000). PPP2CA is the target gene of miRNA-133a and its expression was inhibited by miRNA-133a acting on PPP2CA mRNA 3ʹUTR ( P =  .013). The plasma sVE-cadherin levels in the acute KD groups were increased compared with the control group ( P =  .024). The ROC curve analysis showed that the expression of miRNA-133a segregate acute KD patients from convalescent KD patients and healthy children. Our results suggest that miRNA-133a might be a new biomarker for KD.